Sentiment of Bangladeshi residents toward Covid-19 lockdowns: Qualitative analyses of open-ended responses in a large panel survey - Collins, Daryl; Moore, Derry; Battula, Pravarakya Reddy; Faruk, Avinno (BIGD, 2024)
This paper explores the public sentiment of Bangladeshi residents concerning the lockdowns imposed by the Bangladeshi government in 2021 in response to COVID-19. Through open-ended question design and analyses of natural language using NLP and sociolinguistic techniques, we show detailed, nuanced sentiments as well as common themes and discussions these sentiments are seated. Additionally, using a range of discursive analytical measures, we explore the interactions between enumerators and participants in live survey conditions, providing alternative methods to and potential field guidance for enumerator survey methods.